Do Health Expenditures Converge Among ASEAN Countries? - Li, Zheng-Zheng; Liu, Guangzhe; Tao, Ran; Lobont, Oana-Ramona (Frontiers in Public Health, 2021)
This paper aims to determine the existence of convergence in health expenditures among ASEAN countries. Based on the SPSM procedure and panel KSS unit root test results, the public health expenditures in Indonesia, Lao PDR, Cambodia, the Philippines and Myanmar are converging, while that of Brunei Darussalam, Malaysia, Vietnam, Singapore and Thailand are diverging. In addition, the sequences of private health expenditures in ASEAN member states are stationary, which implies the convergence. This finding is accordance with the Wagner’s law (1), that is, as nations develop, they are forced to expand the public expenditures. Specifically, countries with low levels of public health expenditures tend to catch up with the high health spending countries. This research suggests the policy implications with regard to the convergence of health expenditures across countries. The government in low- and lower-middle income countries should raise the public health expenditures to provide them access to health service for those who are unaffordable individuals (2).